The presence of High-impact factor Open Access Journals in Science, Technology, Engineering and Medicine (STEM) disciplines - Annarita Barbaro; Monica Zedda; Donatella Gentili; Rafael Greenblatt (JLIS.it, 2015)
The present study means to establish to what extent high-quality open access journals are available as an outlet for publication, by examining their distribution in different scientific disciplines, including the distribution of those journals without article processing charges. The study is based on a systematic comparison between the journals included in the DOAJ, and the journals indexed in the Journal Citation Reports (JCR) Science edition 2013, released by Thomson Reuters. The impact factor of Open Access (OA) journals was lower than those of other journals by a small but statistically significant amount. Open access journals are present in the upper quartile (by impact factor) of 85 out of 176 (48.8%) categories examined. There were no OA journals with an Impact Factor in only 16 categories (9%).